Chinese red pepper (Zanthoxylum bungeanum Maxim.) leaf extract as natural antioxidants in salted silver carp (Hypophthalmichthys molitrix) in dorsal and ventral muscles during processing. (October 2015) - Li, Junke; Hui, Teng; Wang, Fulong; Li, Shun; Cui, Baowei; Cui, Yuqing; Peng, Zengqi
Abstract: Chinese red pepper ( Zanthoxylum bungeanum Maxim.) leaf (ZML) extract contains high amounts of phenolic compounds possessing high total antioxidant capacity and hydroxyl, 1, 1-dipheny-2-picrylhydrazyl (DPPH) free radical scavenging activity. ZML extract was investigated as a natural antioxidant for the lipid stability of salted silver carp ( Hypophthalmichthys molitrix ) throughout salting and drying. Both dorsal and ventral muscles were examined for differences in moisture content, salt content, total lipid content, and degree of lipid oxidation. The hexanal content, Thiobarbituric acid reactive substances (TBARS) value, and lipoxygenase (LOX) activity in the ventral muscle were significantly higher than those of the dorsal muscle ( p < 0.05). In the treatments with ZML extract, the hexanal content, the TBARS value, and the LOX activity were significantly lower ( p < 0.05) during processing both in the dorsal and ventral muscles. The sensory qualities of processed salted fish could be improved with the amount of 0.030% extract in the dorsal muscle and 0.045% extract in the ventral muscle. These results showed that ZML extract can be a source of natural antioxidants and used as a food additive. Highlights: The ventral muscle had higher hexanal content, TBARS values, and LOX activity than dorsal muscle. An amount of 0.030% ZML extracts can inhibit lipid oxidation in the dorsal muscle. Lipid oxidation in the ventral muscle can be retarded by 0.045% ZML extracts. ZML extracts displayed a protective effect against lipid oxidation of salted fish. ZML extract can be a source of natural antioxidants and used as a food additive.